2023
DOI: 10.1108/bfj-11-2022-1031
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable strategies of industrial tourism in the agri-food business: an exploratory approach

Abstract: PurposeThis study aims to analyze the opportunities and potential of industrial tourism for the agri-food industry in the current post-pandemic scenario. Industrial tourism can favor appropriate behaviors by companies and tourists to address emerging challenges in the post-pandemic era, such as responsible production and consumption and the containment of waste production.Design/methodology/approachThe adopted research method is a case study with exploratory purposes, applied to an industrial tourism experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The industrial tourism has been defined as “visits to sites that enable residents and tourists to learn about a region’s operational activities through visits to, and tours of, active business and corporate museums founded by companies with a long history strongly rooted and/or typical in the area, as well as producers of cultural foods, and sometimes bearers of status symbols such as typical products”. In this context, Badia et al . (2024) have analyzed the opportunities and potential of industrial tourism for the agri-food companies in the post-pandemic scenario.…”
Section: Overview Of the Papers Included In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The industrial tourism has been defined as “visits to sites that enable residents and tourists to learn about a region’s operational activities through visits to, and tours of, active business and corporate museums founded by companies with a long history strongly rooted and/or typical in the area, as well as producers of cultural foods, and sometimes bearers of status symbols such as typical products”. In this context, Badia et al . (2024) have analyzed the opportunities and potential of industrial tourism for the agri-food companies in the post-pandemic scenario.…”
Section: Overview Of the Papers Included In The Special Issuementioning
confidence: 99%
“…The industrial tourism has been defined as "visits to sites that enable residents and tourists to learn about a region's operational activities through visits to, and tours of, active business and corporate museums founded by companies with a long history strongly rooted and/or typical in the area, as well as producers of cultural foods, and sometimes bearers of status symbols such as typical products". In this context, Badia et al (2024) have analyzed the opportunities and potential of industrial tourism for the agri-food companies in the postpandemic scenario. On the basis of the results of a case study, the research highlights that industrial tourism in agri-business allows for a nexus between companies and local areas and can strengthen sustainable strategies and choices for organizations and customers, such as sustainable business tours as a mean of attractiveness for travelers.…”
Section: Circular Economy and Sustainable Strategies In Tourismmentioning
confidence: 99%
“…The research revealed insight into the importance of the experiential qualities of heritage tourism-specifically those aligned to the natural environment-and a desire to achieve an emotive and sensual engagement with key signifiers of both tangible and intangible cultural heritage through potential leisure experiences (Manley et al, 2023). For example, a business tour is a distinctive component of an experiential tourism offering that helps consumers better understand the food production process while respecting environmental and social values (Badia et al, 2023).…”
Section: B Literature Review Experiential Tourismmentioning
confidence: 99%